Acellularized spinal cord scaffolds incorporating bpV(pic)/PLGA microspheres promote axonal regeneration and functional recovery after spinal cord injury. Issue 32 (18th May 2020) - Liu, Jia; Li, Kai; Huang, Ke; Yang, Chengliang; Huang, Zhipeng; Zhao, Xingchang; Song, Shiqiang; Pang, Taisen; Zhou, Jing; Wang, Yuhai; Wang, Chong; Tang, Yujin
Abstract : Spinal cord injury (SCI) is a traumatic injury to the central nervous system (CNS) with a high rate of disability and a low capability of self-recovery. Abstract : Spinal cord injury (SCI) is a traumatic injury to the central nervous system (CNS) with a high rate of disability and a low capability of self-recovery. Phosphatase and tensin homolog (PTEN) inhibition by pharmacological blockade with bisperoxovanadium (pic) (bpV(pic)) has been reported to increase AKT/mTOR activity and induce robust axonal elongation and regeneration. However, the therapeutic effect of bpV(pic) in treating SCI is limited due to the lack of efficient delivery approaches. In this study, a composite scaffold consisting of an acellular spinal cord (ASC) scaffold and incorporated bpV(pic) loaded poly (lactic- co -glycolic acid) (PLGA) microspheres was developed, in order to improve the therapeutic effect of bpV(pic) on SCI. The inhibition of PTEN activity and activation of the mTORC1/AKT pathway, the axonal regeneration and the markers of apoptosis were analyzed via western blot and immunofluorescence in vitro . The bpV(pic)/PLGA/ASC scaffolds showed excellent biocompatibility and promoted the viability of neural stem cells and axonal growth in vitro . Implantation of the composite scaffold into rats with hemi-sectioned SCI resulted in increased axonal regeneration and functional recovery in vivo . Besides, bpV(pic) inhibited the phosphorylation of PTEN and activated the PI3K/mTOR signaling pathway. The successful construction of the composite scaffold improves the therapeutic effect of bpV(pic) on SCI.